1998
DOI: 10.1046/j.1525-1438.1998.09758.x
|View full text |Cite
|
Sign up to set email alerts
|

Early ovarian cancer: Is there a role for systematic pelvic and para-aortic lymphadenectomy?

Abstract: Baiocchi G, Raspagliesi F, Grosso G, Fontanelli R, Cobellis L, di Re E, di Re F. Early ovarian cancer: Is there a role for systematic pelvis and para‐aortic lymphadenectomy? Int J Gynecol Cancer 1998; 8: 103–108. In order to focus on the incidence and the clinical significance of lymphatic spread in patients with cancer apparently confined to the ovaries, we present our 20 year experience in a large series of patients with early ovarian cancer who had systematic pelvic and para‐aortic lymphadenectomy. A retros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 28 publications
2
33
1
Order By: Relevance
“…26 Baiocchi et al reported a rate of lymph node involvement of 12.9% and 14.7% in patients with Stage IA and IB disease, respectively. 18 These rates according to the grade were 3.9% in Grade 1, 7.7% in Grade 2, and 38.5% in Grade 3 Stage I tumors, respectively. 18 In the series reported by Meier, 5% and 39% of patients with Grade 2 and 3 tumors had lymph node involvement.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…26 Baiocchi et al reported a rate of lymph node involvement of 12.9% and 14.7% in patients with Stage IA and IB disease, respectively. 18 These rates according to the grade were 3.9% in Grade 1, 7.7% in Grade 2, and 38.5% in Grade 3 Stage I tumors, respectively. 18 In the series reported by Meier, 5% and 39% of patients with Grade 2 and 3 tumors had lymph node involvement.…”
Section: Discussionmentioning
confidence: 86%
“…18 These rates according to the grade were 3.9% in Grade 1, 7.7% in Grade 2, and 38.5% in Grade 3 Stage I tumors, respectively. 18 In the series reported by Meier, 5% and 39% of patients with Grade 2 and 3 tumors had lymph node involvement. 26 Such patients were upstaged to Stage IIIC disease.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Up to 10-25% of patients with presumable early stage disease which is confined to the ovaries or pelvis are upstaged after thorough surgical staging procedure due to pelvic lymph node metastasis. [18][19][20][21] Paraaortic lymph nodes were positive in 6% of these patients. 19 Because lymph node involvement is an important prognostic factor, 7-9,22 patients with metastasized lymph nodes is assigned stage IIIC even if their intraperitoneal disease is equivalent to stage I-IIIB according to the FIGO staging system for ovarian cancer.…”
Section: Discussionmentioning
confidence: 99%
“…More than one-third of poorly differentiated (grade 3) tumors had node metastases. 14,16 The distribution of positive nodes has been described by minute investigation. In macroscopic unilateral ovarian cancer, involvement of the ipsilateral pelvic node alone was found as the most frequent (56.4%).…”
Section: Lymph Drainage Pathwaymentioning
confidence: 99%